PERAN IAIN PONTIANAK DALAM PENCEGAHAN PEMAHAMAN RADIKALISME AGAMA - Hamka Siregar (AT-TURATS, 2015)
The historicity of the State Institute of Islamic Studies (IAIN) Pontianak actually brings us to an understanding that in fact IAIN Pontianak has so far taken part in preparing alumni who are skilled and competent in the field of Islamic religious sciences, such as Islamic education, Islamic law, and Islamic dakwa. This also signifies the responsibility of IAIN Pontianak in shaping the ‘considerate and tolerant understanding of religion’ and minimizing forms of religious radicalism on campus. This will be discussed further in this paper.